Is it the time of seno-therapeutics application in cardiovascular pathological conditions related to ageing? - Carmela Rita Balistreri; Rosalinda Madonna; Peter Ferdinandy (Elsevier, 2021)
It rates that in 2030, the cardiovascular diseases (CVD) will result in 40% of all deaths and rank as the leading cause. Thus, the research of appropriate therapies able to delay or retard their onset and progression is growing. Of particular interest is a new branch of the medical science, called anti-ageing medicine since CVD are the result of cardiovascular ageing. Senescent cells (SC) accumulate in cardiovascular system contributing to the onset of typical age-related cardiovascular conditions (i.e., atherosclerosis, medial aorta degeneration, vascular remodeling, stiffness). Such conditions progress in cardiovascular pathologies (i.e., heart failure, coronary artery disease, myocardial infarction, and aneurysms) by evocating the production of a proinflammatory and profibrotic senescence-associated secretory phenotype (SASP). Consequently, therapies able to specifically eliminate SC are in developing. The senotherapeutics represents an emerging anti-SC treatment, and comprises three therapeutic approaches: (a) molecules to selectively kill SC, defined senolytics; (b) compounds able in reducing evocated SC SASP, acting hence as SASP suppressors, or capable to change the senescent phenotype, called senomorphics; (c) inhibition of increase of the number of SC in the tissues. Here, it describes them and the emerging data about current investigations on their potential clinical application in CVD, stressing benefits and limitations, and suggesting potential solutions for applying them in near future as effective anti-CVD treatments.